Cover Image, Volume 86, Issue 8, August 2019. Issue 8 (12th August 2019) - Eini, Fatemeh; Bidadkosh, Arash; Nazarian, Hamid; Piryaei, Abbas; Ghaffari Novin, Marefat; Joharchi, Khojasteh
Abstract : Cover Caption : The cover image is based on the Research Article Thymoquinone reduces intracytoplasmic oxidative stress and improves epigenetic modification in polycystic ovary syndrome mice oocytes, during in‐vitro maturation by Fatemeh Eini et al., https://doi.org/10.1002/mrd.23222 . Credit: Cover image © Dr. Fatemeh Eini Images.